The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1101/2021.06.03.21258300
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Field evaluation of specificity and sensitivity of a standard SARS-CoV-2 antigen rapid diagnostic test: A prospective study at a teaching hospital in Northern Ghana

Abstract: Background: The testing capacity for SARS-CoV-2 in Africa is rather limited. Antigen-detection rapid diagnostic tests (Ag-RDTs) are a cheap and rapid alternative to reverse transcriptase-polymerase chain reaction (RT-PCR) tests, but there is little data about their performance under real life conditions in tropical countries. Objective: To evaluate the performance of a standard Ag-RDT in a population of a major hospital in northern Ghana. Methods: Prospective, cross-sectional, blinded verification of the perfo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…At the end of the data extraction process, 21 studies were still in preprint form [20,21,25,51,54,59,62,69,73,78,88,104,120,125,133,164,171,172,177,178,190]. All studies included were written in English, except for 3 in Spanish [57,66,138], 1 in Turkish [99], and 1 in French [157].…”
Section: Summary Of Studiesmentioning
confidence: 99%
“…At the end of the data extraction process, 21 studies were still in preprint form [20,21,25,51,54,59,62,69,73,78,88,104,120,125,133,164,171,172,177,178,190]. All studies included were written in English, except for 3 in Spanish [57,66,138], 1 in Turkish [99], and 1 in French [157].…”
Section: Summary Of Studiesmentioning
confidence: 99%
“…This finding is significant and may partially explain false negative results, considering that many regions have oscillations in temperature outside the target range and some factors like stock storage and transportation are beyond the end-user control. In this context, Abdul-Mumin et al 138 reported suboptimal results for both sensitivity and specificity using the STANDARD Q COVID-19 test (64% and 81%, respectively); authors reported the difficulty of maintaining the tests within the ideal temperature range near patients given the temperatures in Ghana, despite following the manufacturer’s storage conditions. Therefore, for optimal results, it is important to consider not only the performance of the tests but also context they are being used in.…”
Section: Discussionmentioning
confidence: 99%
“… In patients with signs and symptoms compatible with COVID-19, we suggest the use of laboratory based NAAT in nasopharyngeal samples versus rapid antigen detection testing in nasopharyngeal samples for the diagnosis of COVID-19. Weak against Very low [ 4 , 5 , 16 , 106 , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , 6 , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , 8 , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , 10 , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , 11 , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] ...…”
Section: Questions Addressed By the Guideline Updatementioning
confidence: 99%
“… In patients with signs and symptoms compatible with COVID-19 of equal or less than 7 days-onset, we suggest the use of rapid antigen detection testing versus laboratory-based NAAT for the diagnosis of COVID-19. Weak for Very low [ 3 , 7 , 39 , 41 , 46 , 53 , 60 , 61 , 63 , 65 , 73 , 78 , 9 , 79 , 83 , [91] , [92] , [93] , 96 , 97 , 100 , 101 , 104 , 11 , 106 , 108 , 109 , 114 , 118 , 119 , 126 , [129] , [130] , [131] , 13 , [132] , [133] , [134] , [135] , [136] , 14 , 17 , 21 , 36 , 37 ] 16 In patients with signs and symptoms compatible with COVID-19 of more than 7 days-onset , should rapid antigen detection testing be used, compared with standard NAAT (commercial and/or in house) for diagnosis of COVID-19? In patients with signs and symptoms compatible with COVID-19 of more than 7 days-onset, we suggest the use of laboratory-based NAAT versus rapid antigen detection testing for the diagnosis of COVID-19.…”
Section: Questions Addressed By the Guideline Updatementioning
confidence: 99%
See 1 more Smart Citation